Knowledge banks? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Libraries have long been a society's store of knowledge. No longer staffed just by bookworms and book lovers, and often demand-led, they are stepping firmly into the future.Ancient and modernStand, early one morning, at the side of a major road out...